Utilization of paneer whey in ice candy type frozen dessert - Parmar, Satishkumar Chaturbhai; Jain, Amit Kumar; Aparnathi, Kishorkumar (Indian Journal of Dairy Science, 2017)
Whey and whey components are being used in several dairy and food products i.e. beverages, soups, sports drinks, etc. One of the possible means of utilization of whey is its incorporation into ice candy. In this study, paneer whey was incorporated as replacement of water in preparation of candy mix. Candies prepared from mix incorporated with paneer whey scored better over control on sensory evaluation. For optimization of rate of paneer whey addition, different proportions of whey (i.e. 33, 67 and 100% whey) were tried to replace water. The candies with 67 per cent whey was found to be better in sensory attributes. For selection and optimization of sweetening agents in candy, liquid glucose, dextrose and maltitol were tried. The amount of sucrose was kept constant (240g/L). The overall acceptability of candies with 35g liquid glucose was found to be better. For selection and optimization of amount of stabilizers; pectin, CMC, modified starch, alginate and guar gum were tried. Pectin at the level of 1.5g was found to significantly improve sensory parameters like body and texture, melting characteristics and overall acceptability of candies. Different flavours (mango, orange, pineapple, kalakhatta and khus) were tried for their suitability and were found acceptable. However, candies with mango flavour were preferred the most. Candies were analyzed for gross chemical composition. The total solids, protein, ash, fat and total carbohydrates of the candies prepared from optimized formulation were found to be 35.60, 0.32, 0.37, 0.37 and 34.54 per cent, whereas, for that of control candies these values were 27.90, 0.14, 0.003, 0.0 and 27.78 per cent respectively. The acidity (% citric acid) and â°Brix of the optimized formulation were 0.53 and 32, whereas, that of control were 0.33 and 25 respectively.